ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BELAJAR SISWA MATA PELAJARAN IPS (STUDI KASUS KELAS VII PADA SMP NEGERI 1 NGUNUT TULUNGAGUNG): (Studi Kasus Kelas VII pada SMP Negeri 1 Ngunut Tulungagung) - Layla Fadlilatus Sholikhah; Muhammad Anasrulloh (FKIP Unswagati, 2025)
This study aims to analyze the learning interest of students and identify the internal and external factors influencing it in Social Sciences (IPS) subject for seventh-grade students at SMP Negeri 1 Ngunut Tulungagung during the 2024/2025 academic year. Employing a qualitative descriptive approach, data were collected through observation, in-depth interviews with teachers and five high-interest seventh-grade students, and documentation. Data analysis was conducted using Miles and Huberman's interactive model, which includes data reduction, data display, and conclusion drawing. Data validity was tested through source triangulation. The results indicate that the learning interest of IPS students in Class VII at SMP Negeri 1 Ngunut is generally good, supported by the variety of teaching methods applied by the teacher. The dominant factors influencing learning interest include internal factors (health, motivation, and student attitude) and external factors (parental relationships, teacher's role, and social environment including peers). These findings suggest that student learning interest is a complex phenomenon influenced by multidimensional interactions from within the students themselves and their surrounding environment. The implications of this research emphasize the importance of a holistic approach in learning strategies and educational ecosystem support to foster sustainable learning interest. Keywords: learning interest, internal factors, external factors, social sciences, economic education